Hydrogeochemistry of fluoride-enriched groundwater in Khaled-Abad basin, semi-arid region of Central Iran - Kaveh Pazand; Nasrin Aghavali (Applied Water Science, 2022)
Abstract Due to the decrease in rainfall in Iran and the lack of water consumption, especially in arid and semi-arid regions of the country, groundwater is of special importance as the only source of water in these areas. Groundwater samples were sampled from 28 wells stations and observe turned, to determination the fluoride value in groundwater of the Khaled-Abad basin. The variation in the quantity of fluoride in groundwater samples is adjustment from 0.3 to 8.6 mg/l and an average value is 2.8 mg/l. Generally, 75% of the samples contained fluoride concentrations more than the drinking water standard. The outcomes of this study infer that basement rocks embody epidote, biotite and apatite and the principal supply of fluoride inside the region's groundwater sources is weathering of those minerals.